Internal Quality Assurance System (Case Study of Model School in State Junior High School Sambas 1 (SMPN 1 Sambas)) - Sri Kurnia; Sukmawati Sukmawati; Muhammad Chiar (JETL (Journal of Education, Teaching and Learning), 2019)
The model school is considered to be a great school, even though in reality, the word "model" in the model school is the system, namely theInternal quality assurance system (SPMI) being modeled at the school. The purpose of this study is to describe the Internal Quality Assurance System (case study at the SMPN 1 Sambas. Research conducted by using a qualitative approach with a type of case study research. The stages in this study consist of the stages of preparation, implementation, and reporting. Based on the research that has been done, the following results are obtained. (1) All components in implementing the School's Internal Quality Assurance System Model at SMPN 1 Sambas have been fulfilled by the Head of SMPN 1 Sambas with an average score of 84.34 from a maximum/100 score ; (2) In the process of the School's Internal Quality Assurance System the model in SMPN 1 Sambas has gone through the stages of planning, implementation and supervision in accordance with the provisions and carried out appropriately; (3) Output of the School's Internal Quality Assurance System in SMPN 1 Sambas works well; and (4) Barriers to the Model School's Internal Quality Assurance System in SMPN 1 Sambas, among others, a complete and correct lack of understanding of teachers and education personnel on the Internal Quality Assurance System, the assumption that principals are responsible for guaranteeing, improving, and civilizing quality and funds inadequate. The conclusion obtained from this research is that the Internal Quality Assurance System at SMPN 1 Sambas has been running well even though there are some obstacles, but it can be handled well.